Transformational Leadership and Employee Motivation in Hungary: The Influence of Age, Educational Attainment and Work Experience - Al-Kayyal, Rua; Varga , Erika; Szabó , Katalin (Acta Carolus Robertus, 2024)
This quantitative study investigates the influence of demographic variables such as age, educational attainment, and work experience on work motivation in the presence of transformational leadership among employees in private organizations in Hungary. Through rigorous ANOVA tests and Bonferroni post-hoc comparisons, the research aimed to understand the impact of these variables on individuals' motivation in the existence of transformational leadership. Utilizing a cross-sectional survey method, data were collected from a diverse sample of employees representing various industries and demographic backgrounds. Participants rated their motivation levels using a Likert scale across the four dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The findings reveal no significant differences in motivation levels across different demographic groups, challenging the notion that demographic characteristics alone predict work motivation. The research highlights the presence of other intricate factors or contextual nuances that may exert greater influence on motivational dynamics within organizations. These results underscore the importance of considering additional contextual factors and effective leadership practices in fostering motivation at the workplace. The study contributes to our understanding of motivational dynamics within organizational settings and highlights the need for a holistic approach to enhancing employee motivation.